Investigating the geographical distribution of skin cancer (BCC type) in Ardabil province via GIS - Mohebbipour, Alireza; Alipour, Saeid; Ahari, Saeid Sadeghiyeh; Amani, Firouz; Farzaneh, Esmaeil (International Journal of Research in Medical Sciences, 2017)
Background: Skin cancer is the most common type of cancer in most countries and it holds the first or the second place in terms of frequency in different areas of the country. BCC is the most usual type of tumor in the white skinned people, and its incidence rate rises as individuals get older, especially after age 40.Thistype of skin cancer mostly occurs in the white skinned people and, in85% of cases; it develops on the head and neck. This study aimed at examining the geographical distribution of skin cancer (BCC type) in Ardabil province through GIS. Methods: This cross-sectional study has been done on 131 cases of skin cancer with type BCC in 2007-2014. The required information such as age, sex, occupation, and the locus of BCC, was extracted from the patients' records based on their place of residence. Data analysis was performed using SPSS (version 20). ARC GIS (version 10) was used for drawing geographic maps. Results: 50.4% of the subjects were men and the mean age of them was 62.8±14.5 years. Of the subjects, 66.4% were from Ardabil city, 80.2% from urban population and 15.3% of the subjects were smokers. Of the patients, 78.5% had developed cancer in their face. Conclusions: Results showed that for control of cancer, educational interventions should be given priority, and people should be instructed about the use of personal protection equipment, like proper sunscreen cream, hat and sunshade in the workplace, as far as it is possible.